Sistem Pendukung Keputusan Pemilihan Jurusan Menggunakan Metode TOPSIS Berbasis Web Studi Kasus: SMK Negeri 38 Jakarta Pusat - Khasanah, Fitri Nur; Whendasmoro, Raditya Galih; Sharyanto, Sharyanto (FIKOM - Bung Karno University, 2023)
The selection of majors at SMK Negeri 38 Jakarta currently relies on a single opportunity during registration, without considering various factors that might influence students' choices. This underscores the necessity for developing a decision support system that can aid prospective students in selecting majors aligned with their interests, potentials, and characteristics. The aim of this research is to design and implement a decision support system using the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) method as an alternative to facilitate a more informed decision-making process. The research methodology involves data collection from prospective students, including personal interests, the average grades from the first to the fifth semester of junior high school, average school examination scores, registration pathways, and percentiles of grades. This data serves as input for the TOPSIS method to generate recommendations for study focus options that suit the characteristics of each prospective student. The research findings indicate that the implementation of a TOPSIS-based decision support system offers a more accurate possibility for major selection, aligning with the potentials and interests of prospective students. This system allows for data filtering and processing to produce recommendations guiding prospective students in choosing a suitable study focus among three available options: Hospitality, Culinary Arts, and Fashion Design. Conclusively, the decision support system using the TOPSIS method proves to be an effective solution in aiding new prospective students at SMK Negeri 38 Jakarta in selecting majors aligned with their interests and potentials, thereby reducing the tendency for errors in major selection based on a single registration opportunity.